2010 Breast Symposium: Plenary Lecture - APPLE, SOPHIA K (Indonesian Journal of Cancer, 2010)
2010 Breast Symposium: Plenary LectureÂ Full text : http://www.scribd.com/doc/43599485/2010-Breast-Symposium-Plenary-Lecture